Chapter 34 Digital Learning for Development of Asian Schools - J. Kennedy, Kerry; Chi-Kin Lee, John; Ping Lim, Cher (Taylor & Francis, 2018)
Despite the potential of digital technologies to contribute to the enhancement of access to quality education and the development of lifelong learning competencies, many knowledge gaps remain in how, for whom and in what contexts digital technologies actually do contribute to improved, equitable educational outcomes. More research is needed that creates and tests 'proven models' of digital learning in Asian schools and deepens our understanding of the conditions that are necessary and sufficient for success. And this research needs to build on the research that has already been done in the region and worldwide. The primary aim of this book section is to provide snapshots of the current state in research and to identify and explain the research gaps and future directions of digital learning for development in Asian schools.